Differences in habitat complexity between restored and natural seagrass meadows shape fish community structure - Julia Castro-Fernández; Inés Castejón-Silvo; Hilmar Hinz; Aleida Escandell Westcott; Jorge Terrados (Nature-Based Solutions)
Seagrass meadows play a crucial role in providing essential ecosystem functions and services, serving as habitat and nursery areas for numerous fish species. Seagrass structural complexity is a key factor influencing these functions. The alarming degradation rate of seagrass beds has boosted research into restoration efforts as Nature-Based Solutions, aimed at recovering meadow structure and associated functions. A comprehensive understanding of how fish communities respond to seagrass restoration is necessary to quantify the ecosystem services in restored areas. This study evaluates the restoration progress of habitat structure in a rehabilitated Posidonia oceanica meadow and the fish communities inhabiting this area, encompassing juvenile and adult fish populations. The structural recovery dynamics of the restored meadow and its fish assemblages were compared to those in the inner and edge areas of a natural reference meadow. In situ measurements of habitat complexity were taken, while fish communities were evaluated through diver-operated stereo-video transects. The restored area exhibited reduced structural complexity, lower juvenile and adult species richness, total density, and biomass compared to reference areas, with a distinct species composition. Differences were more pronounced for adults than juveniles, suggesting that after a three-year recovery period, the restored area may provide food and shelter for some juvenile species but remains inadequate for adults. Although some fish utilize the restored area, reference levels for the habitat and nursery functions have not been attained yet. Further research on the long-term evolution of the state of ecosystem functions following restoration actions is critical for assessing potential effective technical measures of replanting that may help accelerate the recovery rates of these functions to reference levels.